2012
DOI: 10.1016/j.bbr.2011.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of the GluK4 kainate receptor subunit causes anxiolytic and antidepressant-like behavior in mice

Abstract: There is a clear link between dysregulation of glutamatergic signaling and mood disorders. Genetic variants in the glutamate receptor gene GRIK4, which encodes the kainate receptor subunit GluK4, alter the susceptibility for depression, bipolar disorder and schizophrenia. Here we demonstrate that Grik4−/− mice have reduced anxiety and an antidepressant-like phenotype. In the elevated zero-maze, a test for anxiety and risk taking behavior, Grik4−/− mice spent significantly more time exploring the open areas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 60 publications
3
43
0
Order By: Relevance
“…Hipsignificant impairment in MF-CA3 LTP(Catches et al, 545 2012). Expression of the GluK4 receptor subunit is546 restricted to the CA3 region and DG regions of the hip-547 pocampus in which kainate receptors are known to mod-548 ulate synaptic plasticity(Catches et al, 2012). In the 549 present study, we found that MS induced an increased550 anxiety and decreased LTP at MF-CA3 synapse.…”
mentioning
confidence: 53%
“…Hipsignificant impairment in MF-CA3 LTP(Catches et al, 545 2012). Expression of the GluK4 receptor subunit is546 restricted to the CA3 region and DG regions of the hip-547 pocampus in which kainate receptors are known to mod-548 ulate synaptic plasticity(Catches et al, 2012). In the 549 present study, we found that MS induced an increased550 anxiety and decreased LTP at MF-CA3 synapse.…”
mentioning
confidence: 53%
“…Differential methylation was detected in Grin 1 , the gene for the NMDA NR1 subunit, in Grik3 and Grik4 , the genes for KA receptor subunits, in genes for glutamate receptor interacting proteins such as Grip1 , and Shank1, 2, 3 as well as in calcium ( Cacna1c ) and potassium channel ( Kcnj) genes that can all influence neuronal excitability and modulate anxiety. 58, 59, 60, 61 …”
Section: Discussionmentioning
confidence: 99%
“…These included GRIK4 (kainate glutamate receptor subtype), cholinergic receptor nicotinic alpha 4 (CHRNA4) (encodes for a subtype of neuronal nicotinic acetylcholine receptor), disrupted in schizophrenia-1 (DISC-1), ErbB4, and neuregulin-1 (NRG-1). Kainate receptor, GluK4 knockout adult mice show hyperactivity and impaired pre-pulse inhibition(Lowry et al 2013), while Grik4 knockout adult mice show reduced anxiety and antidepressant behaviour(Catches et al 2012). However, both of these studies only assessed male mice, therefore no sex comparisons have been made here.…”
mentioning
confidence: 99%